System Xc−/GSH/GPX4 axis: An important antioxidant system for the ferroptosis in drug-resistant solid tumor therapy - Li, Feng-Jiao; Long, Hui-Zhi; Zhou, Zi-Wei; Luo, Hong-Yu; Xu, Shuo-Guo; Gao, Li-Chen (Frontiers in Pharmacology, 2022)
The activation of ferroptosis is a new effective way to treat drug-resistant solid tumors. Ferroptosis is an iron-mediated form of cell death caused by the accumulation of lipid peroxides. The intracellular imbalance between oxidant and antioxidant due to the abnormal expression of multiple redox active enzymes will promote the produce of reactive oxygen species (ROS). So far, a few pathways and regulators have been discovered to regulate ferroptosis. In particular, the cystine/glutamate antiporter (System Xc-), glutathione peroxidase 4 (GPX4) and glutathione (GSH) (System Xc-/GSH/GPX4 axis) plays a key role in preventing lipid peroxidation-mediated ferroptosis, because of which could be inhibited by blocking System Xc-/GSH/GPX4 axis. This review aims to present the current understanding of the mechanism of ferroptosis based on the System Xc-/GSH/GPX4 axis in the treatment of drug-resistant solid tumors.